Genetic diversity and phylogeny analysis of azolla based on dna amplification by arbitrary primers - Coppenolle, Benoit Van; Watanabe, Iwao; Hove, Charles Van; Second, Gerard; Huang, Ning; McCouch, Susan R. (Canadian Science Publishing, 1993)
The polymerase chain reaction was used to amplify random sequences of DNA from 25 accessions of Azolla to evaluate the usefulness of this technique for identification and phylogenetic analysis of this aquatic fern. Accessions were selected to represent all known species within the genus Azolla and to encompass the worldwide distribution of the fern. Primers of 10 nucleotides with 70% G + C content were used to generate randomly amplified polymorphic DNA from the symbiotic Azolla–Anabaena complex. Twenty-two primers were used and each primer gave 4–10 bands of different molecular weights for each accession. Bands were scored as present or absent for each accession and variation among accessions was quantified using Nei's genetic distances. A dendrogram summarizing phenetic relationships among the 25 accessions was generated using the unweighted pair-group method with arithmetic mean. Principal component analysis was also used to evaluate genetic similarities. Three distinct groups were identified: group 1 contains five species, group 2 contains the pinnata species, and group 3 contains the nilotica species. The analysis demonstrates that the major groups of Azolla species can be easily distinguished from one an other and, in addition, that closely related accessions within species can be identified. We further found that using 10 primers, a phylogeny that is essentially the same as that derived from 22 primers can be constructed. Our results suggest that total DNA extracted from the Azolla–Anabaena symbionts is useful for classification and phylogenetic studies of Azolla.Key words: Azolla–Anabaena symbiosis, genetic distances, polymerase chain reaction, principal component analysis.